Meningkatkan kesadaran dan budaya K3 melalui strategi pendekatan edukasi praktis di sektor industri kelapa sawit PT X - Hapsari, Restiana Kartika Mantasti; Akbar, Arief Rahmad Maulana; Noor, Meitria Syahadatina; Noor, Ihya Hazairin; Nisa, Mufatihatul Aziza (Penamas: Journal of Community Service, 2025)
This community service activity aims to raise awareness and foster a culture of Occupational Safety and Health (OSH) among workers in the palm oil plantation sector. The program was implemented at PT X, South Kalimantan, targeting field workers in high-risk units. The implementation method employed an interactive and applied educational approach through five stages: preparation, pre-test, educational intervention, post-test, and evaluation. The training was delivered face-to-face through lectures, discussions, and Q&A sessions. The evaluation used pre-and post-test questionnaires to assess participants’ knowledge, attitudes, and behaviors regarding OSH. The results showed an increase in the average score from 75.47 to 82.97, with 71.8% of participants showing improvement. However, 21.8% experienced a decrease in scores, indicating a persistent knowledge-behavior gap influenced by limited education and inaccurate perceptions. Follow-up training is needed using contextual approaches and simple, easy-to-understand educational media. Company management is also encouraged to act actively as role models in fostering a sustainable workplace safety culture.